Adhesion of a glass-ionomer root canal sealer to the root canal wall. - S. Timpawat (2018)
Glass-ionomer root canal sealer is commonly used because of its chemical bonding and favorable physical characteristics when bonding to dentin. This study was designed to determine the tensile bond strength of a glass-ionomer sealer (Ketac Endo, Espe, Seefeld, Germany) on root canal walls after pretreatment with different conditioners. Flat inner surfaces of root canal specimens were prepared. The specimens were divided into five groups of 10 teeth, and the groups were conditioned with one of the following smear layer removal solutions: 15% EDTA/NaOCl, 10% polyacrylic acid, 35% phosphoric acid, 6% citric acid, and 5.25% NaOCl as a control. Then the exposed root canal areas were coated with Ketac-Endo. Tensile bonding was measured using a universal testing machine until ultimate failure was obtained. The groups that were treated with phosphoric acid and citric acid showed significantly higher bond strengths than the groups that were treated with 15% EDTA and polyacrylic acid (p < 0.05). Bonding to dentin without smear layer removal (NaOCl group) was too low to be measured in the testing apparatus. Scanning electron microscopy confirmed that phosphoric and citric acids were more effective in removing smear layer than EDTA or polyacrylic acid. The result supported the view that pretreatment with phosphoric acid or citric acid should be used in association with glass-ionomer root canal sealer to achieve the most effective removal of the smear layer and to provide better adhesion.